Simulation of Stresses in A Drill Using the Ansys Program - Urinov Nasillo Fayzilloevich; Saidova Mukhabbat Khamroevna; Ergashova Surayyo Raxmonovna (Genius Journals, 2022)
The article presents a comparison of the maximum stresses that occur in the drill under the influence of the drilling torque, with the allowable stress, as well as a comparison of the maximum stress that occurs during the manufacture of the drill under the action of the cutting force, in the grinding operation
Keywords: grinding operation; cutting force; finite element mesh; drilling